2019
DOI: 10.35841/2591-7994.3.1-5
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a restrictive blood transfusion protocol in a gynecologic oncology service

Abstract: Objectives: The purpose of this study was to evaluate the impact of a restrictive blood transfusion protocol in a postoperative gynecologic oncology population. The primary objective was the rate of blood transfusions after surgery before and after implementation of a restrictive transfusion protocol (from July 1 st 2011 to December 30 th 2016). Secondary outcomes were patient morbidity and included rates of surgical site infection, pneumonia, sepsis, unplanned intubation, prolonged ventilator use, renal insuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(26 reference statements)
0
1
0
1
Order By: Relevance
“…The study also demonstrated that there was a cost savings of USD$161 112 over 1 year of the intervention without significantly affecting morbidity or mortality 27. Similarly, another institution reported a decrease in transfusion (11.0% to 5.9%, p<0.001), superficial surgical site infection (7.7% to 4.1%, p=0.005), deep surgical site infection (2.3% to 0.7%, p=0.02), and median length of stay (3.0 days to 2.0 days, p>0.001) after implementation of a restrictive transfusion protocol 28. There are also opportunities for improvement in evaluation and treatment of preoperative anemia in gynecologic oncology patients by applying the Using Blood Wisely benchmarks,15 preoperative optimization with intravenous iron,15 and intraoperative tranexamic acid,29 which could impact requirements for transfusion 30…”
Section: Discussionmentioning
confidence: 86%
“…The study also demonstrated that there was a cost savings of USD$161 112 over 1 year of the intervention without significantly affecting morbidity or mortality 27. Similarly, another institution reported a decrease in transfusion (11.0% to 5.9%, p<0.001), superficial surgical site infection (7.7% to 4.1%, p=0.005), deep surgical site infection (2.3% to 0.7%, p=0.02), and median length of stay (3.0 days to 2.0 days, p>0.001) after implementation of a restrictive transfusion protocol 28. There are also opportunities for improvement in evaluation and treatment of preoperative anemia in gynecologic oncology patients by applying the Using Blood Wisely benchmarks,15 preoperative optimization with intravenous iron,15 and intraoperative tranexamic acid,29 which could impact requirements for transfusion 30…”
Section: Discussionmentioning
confidence: 86%
“…A megszorító elvek biztonságosan alkalmazhatónak bizonyultak a legtöbb sebészeti, belgyógyászati ágazatban, a szülészeti és az intenzív osztályos betegeknél is [20][21][22][23]. Az onkológiai betegek esetében a libe-rális elvek érvényesülése alacsonyabb mortalitással járt, így a restrikció erre a betegcsoportra nem vonatkozik [24], a nőgyógyászati onkológiai betegeknél viszont a restriktív értékek alkalmazásának előnyei fi gyelhetők meg [25]. A restrikciós ajánlás alkalmazása azonban kontraindikált hemodinamikai instabilitás és miokardiális iszkémia esetén, súlyos trombocitopeniában és krónikusan transzfúziót igénylő anémiában, valamint elegendő evidencia hiánya miatt akut koronária-szindrómában.…”
Section: áBraunclassified